Comparing Robot-Assisted Laparoscopic Pyeloplasty vs. Laparoscopic Pyeloplasty in Infants Aged 12 Months or Less - Wong, Yuenshan Sammi; Pang, Kristine Kit Yi; Tam, Yuk Him (Frontiers in Pediatrics, 2021)
Objective: To investigate the outcomes of minimally invasive approach to infants with ureteropelvic junction(UPJ) obstruction by comparing the two surgical modalities of robot-assisted laparoscopic pyeloplasty(RALP) and laparoscopic pyeloplasty(LP). Methods: We conducted a retrospective review of all consecutive infants aged ≤ 12 months who underwent either LP or RALP in a single institution over the period of 2008-Jul 2020. We included primary pyeloplasty cases that were performed by or under the supervision of the same surgeon. Results: 46 infants(LP=22; RALP=24) were included with medians of age and body weight at 6 months(2-12months) and 8.0kg(5.4-10kg) respectively. There was no difference between the two groups in the patients’ demographics and preoperative characteristics. All infants underwent LP or RALP successfully without conversion to open surgery. None had intraoperative complications. Operative time(OT) was 242minutes(SD=59) in LP, compared with 225minutes(SD=39) of RALP(p=0.25). Linear regression analysis showed a significant trend of decrease in OT with increasing case experience of RALP(p=0.005). No difference was noted in the postoperative analgesic requirement. RALP was associated with a shorter hospital length of stay than LP(3 vs 3.8 days; p=0.009). 4/22(18%) LP and 3/24(13%) RALP developed postoperative complications(p=0.59), mostly minor and stent-related. The success rates were 20/22(91%) in LP and 23/24(96%) in RALP(p=0.49). Conclusions: Pyeloplasty by minimally invasive approach is safe and effective in the infant population. RALP may have superiority over LP in infants with its faster recovery and a more manageable learning curve to acquire the skills.